Basra under the Ottoman rule, a study describing Basra and its inhabitants during the nineteenth century (Journal of the College of Basic Education, 2023)
Studies that are concerned with life and social reality are among the important studies in understanding reality and lifethe history of societies; Therefore, it has received a wide range of attention in travel books and studiesThe academy - and perhaps the most prominent field of social studies is related to man, his reality and his life 1Therefore, I chose my research to address a specific issue concerned with studying the description of Basra and its inhabitants in terms of structurePopulation, population number, factors and circumstances in light of which the population size: so the studyThe conditions of the residents of Basra were closely linked to the administrative and political reality and the neglect that characterized the conditions ofIraq and the conditions of Basra in particular during the era of the Ottoman Empire, as well as its association with the form ofclose to the health reality; As diseases and epidemics began to kill the population;on public life and on commerce; Therefore, the study of the descriptions of Basra, its conditions, and its inhabitants is of great importanceThe field of historical studies of the conditions of Iraq under the Ottoman administration; In particular, the situation in Basranineteenth century; Various sources have been used in addressing the study of the conditions of Basra and its inhabitants + perhapsThe most prominent of these sources are the books of travelers who visited Basra and reported on its conditions, as well as studiesOther historical academy.